2020
DOI: 10.1101/2020.03.31.011320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A way to break bones? The weight of intuitiveness

Abstract: 21The essential relationship to fat in the Middle Paleolithic, and especially to the yellow 22 42 an innovative GIS (Geographic Information System) method to analyze the distribution of 43 percussion marks to highlight recurrent patterns. 44 One of the most significant results of our article shows the existence of significant concentrations of 45 percussion marks, regardless of the volunteers' behaviour during bone fracturing. The predominance of 46 two factors explains the distribution patterns that emerge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…If we only consider the assemblages with non-random distribution, it is possible to discuss butchery traditions or intuitive patterns. Some works highlight the existence of intuitive patterns in percussion mark distribution for marrow recovery, based on experiments involving non-trained experimenters [ 45 , 46 , 122 ]. Using the results of this experiment and chi-square analysis, we compared whether the non-random distribution of percussion marks is statistically different or not from intuitive pattern distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we only consider the assemblages with non-random distribution, it is possible to discuss butchery traditions or intuitive patterns. Some works highlight the existence of intuitive patterns in percussion mark distribution for marrow recovery, based on experiments involving non-trained experimenters [ 45 , 46 , 122 ]. Using the results of this experiment and chi-square analysis, we compared whether the non-random distribution of percussion marks is statistically different or not from intuitive pattern distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Whether this results from natural or anthropogenic differential preservation (bone fat recovery or fuel), we observed that shaft fragments are much more numerous than epiphyses. Yet, this type of mark is usually located close to the spongy portions [ 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their dataset may therefore be regarded as a null hypothesis according to which the archaeological data could be tested. If Paleolithic patterns of percussion marks differ from Vettese et al's [3] "intuitive" patterns, then the null hypothesis is disproved and one can argue in favor of a learned pattern. The latter can be a result of "culture", as Vettese et al [3] phrase it, in the sense of nonrandom action that draws on transmitted knowledge.…”
mentioning
confidence: 83%
“…If Paleolithic patterns of percussion marks differ from Vettese et al's [3] "intuitive" patterns, then the null hypothesis is disproved and one can argue in favor of a learned pattern. The latter can be a result of "culture", as Vettese et al [3] phrase it, in the sense of nonrandom action that draws on transmitted knowledge. Such comparisons bear a great potential for understanding the degree of technological behavior in the Paleolithic by factoring out the "natural" constraints of bone breakage patterns.…”
mentioning
confidence: 83%
See 1 more Smart Citation